Enzymatic changes in the kidney and brain of freshwater murrel, Channa striatus (Bloch) on short term exposure to sub-lethal concentration of lead nitrate - George, K Roy; Malini, N A; Rajan, Archana; Deepa, R (Indian Journal of Fisheries, 2012)
The effect of short term exposure to sub-lethal concentration (20 ppm) of lead nitrate [Pb(NO3)2] on the activities of alkaline phosphatase, acid phosphatase, succinate dehydrogenase and superoxide dismutase in the kidney and brain of the freshwater murrel, Channa striatus was studied at 24 and 72 h of exposure. The alkaline phosphatase activity was increased, probably due to the adverse effect of lead nitrate on the glucose re-absorption and trans-phosphorylation. The decline in acid phosphatase activity was associated with the tissue damage caused by lead nitrate toxicity. The inhibition of succinate dehydrogenase activity indicated impairment of oxidative metabolic cycle and dependence on the anaerobic glycolytic pathway to meet the energy demands. The reduction in the superoxide dismutase activity revealed an increased oxidative stress on the nervous tissue leading to the lipid peroxidation and damage of brain.